THE STRATEGY OF EXPLORING LOCAL RESOURCES THROUGH THE ROLE OF WOMAN - Suud Marasabessy; Abdullatief Tuasamu (Journal of Management and Business, 2016)
This study aims to identify the potential of local resources that are owned, so that they can be used and developed in order to improve the family's economic level. The results of this study show the employment which entered by the women is mostly in agriculture, forestry, plantation and fishery amounted to 48.51%, and then the trade, hotel and restaurant at 19.18%, in the public service by 18.23%, processing industry (manufacturing) amounted to 10.97%, and others as much as 3.11%. Some commodities of agricultural, plantation, forestry and fishery products such as; sago, tubers, bananas, durian, fish whose production is quite large every year and has the potential to be developed into processed food with economic value but is still not optimal. The position of Salahutu District is geographically very strategic because it is the entrance for the people in the Northern and Eastern hemispheres with the people in the South and West hemisphere. The geographical background effects to the economic wheel rotation in this region to be high, so that if the resources are utilized optimally, it can improve the economic level of the community.